Geomagnetically Conjugate Relationship of Polar Geomagnetic Disturbances -Particularly the Distinct Geomagnetic Conjugacy between Syowa Station in Antarctica and Reykjavik in Iceland - Nagata, Takesi; Kokubun, Susumu; Iijima, T. (1966)
P(論文) In Chapter I, the average pattern of the ionospheric current system of polar geomagnetic storms for the northern and southern polar regions is constructed by analyzing exactly simultaneous events during the IGY period. Those events are classified into two groups; i.e., severe storms where K_P=7.4 and moderate storms where K_p=4.3. In both cases, the average D_p fields for northern and southern polar regions are almost exactly symmetric with each other with respect to the geomagnetic coordinates, suggesting that the geomagnetic linkage holds well between the two polar regions. Several remarks are made on the mechanism of causation of the D_p field. It is emphasized that the D_p field may comprise two components, namely, SP-component which is characterized by enhancement of the S_q^p field by the stronger solar wind in storm time, and defined AEJ-component which has been known as the auroral electrojet concentrating along the narrow region of the auroral zone. In Chapter II, similarity and simultaneity of geomagnetic bay type variations in geomagnetically conjugate areas in the northern and southern polar regions are discussed, based upon simultaneous data of individual bays. From the observed facts, it has been concluded that charged particles of nearly the same flux are precipitating simultaneously in the northern and southern polar ionospheres over the conjugate areas. Besides, it seems likely that nearly the same intensity of electric field is transferred to the both polar regions simultaneously from the magnetosphere. The conjugacy always holds well between the conjugate stations located in the auroral zone and the polar cap at the best-developed stage of geomagnetic bays. Some theoretical discussions are attempted on the structure of instantaneous and individual D_p field of geomagnetic bays. In Chapter III, the conjugacy of storm sudden commencement (SSC) between conjugate points in the auroral zone is described based upon the simultaneous data observed at Syowa Station and Reykjavik. Similarity and ...